STUDI ETNOBOTANI TUMBUHAN OBAT MASYARAKAT SUKU TOPO UMA DI DESA BERDIKARI KABUPATEN SIGI SULAWESI TENGAH - Alvionita Alvionita; Orryani Lambui; Ramadanil Pitopang (Biology Department, Mathematics and natural science, Tadulako University, 2020)
A research entitled Ethnobotanical Studies of Medicinal Plant of Topo Uma Tribe in Berdikari Village Sigi Regency Central Sulawesi has been carried out from December 2016 to February 2017. The research objective was to obtain species of plants used by community of Topo Uma tribe. This research used qualitative and quantitative method. The result showed that there were 56 plants species from 30 families that used by Topo Uma Tribe in Berdikari village. The highest percentace that use in the part of plants were 56,33% of leaves. The processing method is crushed, roasted, pulverized, fried, baked, shredded, boiled, brewed, boiled made cigarette, chewed, cooked as a vegetable, direct attached parts of the body. Types of diseases that are treatable infectious diseases, non-communicable diseases and health care.